Circadian rhythm of VEGF expression in the liver of hepatectomized tumor bearing mice - Andrini, Laura Beatriz (2009)
In this study we analyzed VEGF-C expression in regenerating liver (after partial hepactectomy) of ES2 hepatocellular carcinoma bearing mice, throughout one complete circadian cycle. The animals were sacrificed every 4 h throughout one complete circadian cycle from 26 to 50 h post-hepatectomy. Tumor samples were processed for immunohistochemistry. The expression of VEGF was assessed according to the percentage of immunoreactive cells in a total of 1000 cells (quantitative analysis). The results show that controls and tumor bearing mice have statistical differences at all analysed time points, but the maximun value of VEGF expression of treated animals is significantly higher (p < 0.01) than the control group. We can conclude that when a partial hepatectomy is made with the purpose of eradicating a hepatic tumor, the presence of possible metastasis could release factors related with cellular proliferation that could increase the possibilities of tumoral recidives.